Uji Adaptasi Galur Mutan Harapan Padi Gogo pada Lokasi Lahan Kering Dataran Tinggi Iklim Basah - S.A.N. ARYAWATI; I N. RAI; I G. WIJANA (Agrotrop : Journal on Agriculture Science, 2014)
Adaptation Test of Promising Upland Rice Mutant Line On Dry Highland With Wet Climate. Upland rice productivity is still low, productivity can be improved by using high yielding varieties through the breeding programs, by the Agency for agricultural research (BATAN). Test adaptation is necessary to determine the superiority of promising lines. The objective of this research was to determine adaptability, performance of growth, and productivity of mutant lines of upland rice. Research used randomized complete block design (RAK) single factor with 10 lines of treatment the results of gene mutation and 2 check varieties with three replications. Those treatments were PMG 01/Psj, PMG 02/Psj, PMG 03/Psj, PMG 04/Psj, PMG 05/Psj, PMG 06/Psj, PMG 07/Psj, PMG 08/Psj, PMG 09/Psj, PMG 10/Psj, Limboto and Local. The research was conducted on August 2014 until February 2015 in Tiga Village, District Susut, Bangli regency at high dry land wet climate. Data were analyzed by analysis of variance (Annova) and LSD test at 5% level. The results showed that tested of promising mutant lines show significant differences were observed in all parameters. Treatment of lines PMG 05/Psj, PMG 06/Psj, and PMG 08/Psj gave a yield of 2.22; 2.66; and 3.18 tons GKG/ha or higher than Limboto and Local check varieties as big as 2.04 and 0.90 tones GKG/ha. The three lines showed the parameters of flowering dates, number of filled grain, empty grain, and weight of 1000 grain, harvest time, KAR leaf, and chlorophyll better than check varieties. Lines of PMG 08/Psj gave the results 36.49% higher than Limboto and 71.78% higher than local varieties.